2023
DOI: 10.7150/thno.78736
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Induces M2 Macrophages to Express VSIG4 and Mediate Cardiac Fibrosis After Myocardial Infarction

Abstract: M2 macrophage-mediated tissue repair plays an important role in acute myocardial infarction (AMI). Additionally, VSIG4, which is mainly expressed on tissue-resident and M2 macrophages, is crucial for the regulation of immune homeostasis; however, its effects on AMI remain unknown. In this study, we aimed to investigate the functional significance of VSIG4 in AMI using VSIG4 knockout and adoptive bone marrow transfer chimeric models. We also determined the function of cardiac fibroblasts (CFs) through gain-or l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…A previous study confirmed that in AMI, the expression of IL1R2 in M2‐type macrophages was elevated. 35 Kolbus et al. investigated two subsets of activated CD8+ T cells as predictors of AMI and ischemic stroke during a 15‐year follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study confirmed that in AMI, the expression of IL1R2 in M2‐type macrophages was elevated. 35 Kolbus et al. investigated two subsets of activated CD8+ T cells as predictors of AMI and ischemic stroke during a 15‐year follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study found that hypoxia promotes M2 macrophage intracellular HIF-1α expression and nuclear translocation. It binds to the VSIG4 promoter region, mediating its expression, thereby enhancing the secretion of IL-10 and TGF-β by macrophages, regulating cardiac fibroblast proliferation, migration, and phenotypic transition, and promoting myocardial repair after infarction [ 130 ]. Not only in MI but also in other cardiovascular diseases, this pathway has been shown to affect macrophage function.…”
Section: Macrophages In the Development Of MImentioning
confidence: 99%
“…In the proliferative phase, macrophages are polarized into M2-phenotype macrophages with anti-inflammatory property. 48,49 M2-phenotype macrophages secrete a variety of cytokines, such as TGF-β, IL-10, and VEGF, to promote tissue repair and angiogenesis. 50 At the maturation stage, the recruitment of macrophages ends.…”
Section: The Role Of Different Cells In Heart Recovery Post MImentioning
confidence: 99%